Polysaccharide hydrogels for drug delivery and regenerative medicine - Giri, Tapan Kumar; Ghosh, Bijaya; Badwaik, Hemant (Elsevier, 2024)
Polysaccharide Hydrogels for Drug Delivery and Regenerative Medicine is an archival reference for researchers, students and scientists working on hydrogels based on microbial and animal sources. The book contains Information regarding their synthesis, characterization, and applications in the field of drug delivery and regenerative medicine. Each chapter addresses a separate polysaccharide hydrogel and its suitability in drug delivery and/or regenerative medicine. This is a novel resource that brings together a panel of highly accomplished experts in the field of natural polysaccharides to discuss basic causes and specific problems related to drug delivery and regenerative medicine.